2022
DOI: 10.32615/ps.2022.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of source-sink alteration by pruning on physiological parameters and fruit production of Rosa roxburghii Tratt. on the Yunnan-Guizhou Plateau in China

et al.

Abstract: Highlights• The source alternation can change the distribution of palisade cells and spongy mesophyll in functional leaves • Different pruning methods had a significant effect on the photosynthesis of functional leaves • 50% pruning was more valuable in Roxburgh rose

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Furthermore, research has revealed that the expression of GGP in various plants is significantly regulated by light and undergoes drastic changes under stress [19,69]. Analysis of the GGP promoter sequence has shown that it contains numerous cis-acting elements associated with light response and stress response [70]. Additionally, the light and photosynthesis-dependent rate-limiting enzyme GGP is activated and plays a critical role in the regulation of the ascorbate pool size [71].…”
Section: Overexpressing Rrggp2 and Rrdhar In Tomato Indicates That Rr...mentioning
confidence: 99%
“…Furthermore, research has revealed that the expression of GGP in various plants is significantly regulated by light and undergoes drastic changes under stress [19,69]. Analysis of the GGP promoter sequence has shown that it contains numerous cis-acting elements associated with light response and stress response [70]. Additionally, the light and photosynthesis-dependent rate-limiting enzyme GGP is activated and plays a critical role in the regulation of the ascorbate pool size [71].…”
Section: Overexpressing Rrggp2 and Rrdhar In Tomato Indicates That Rr...mentioning
confidence: 99%
“…Prickly pear leaves have been processed extensively for prickly pear tea due to their unique tea aroma and health effects in the market [ 17 ]. By 2022, the cultivation area of prickly pear had reached 140,000 ha, and the economic value had exceeded USD 2.1 billion [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, China has established itself as the foremost producer and consumer of fruits on a global scale [7,8]. As reported by the FAO [9], between 2012 explored to enhance R. roxburghii yield [49][50][51][52], the potential of orchard intercropping in the context of R. roxburghii cultivation remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%